Eat this, not that! Supermarket survival guide : the no-diet weight loss solution - Zinczenko, David (Rodale, 2009)
Based on the most popular column in both "Men's Health" and "Women's Health" magazines, this work is a comprehensive guide for smart food shopping in the supermarket.